(untitled) (Modern education and development, 2025)
The article "History and Development of Nursing" examines the evolution of nursing from ancient times to modern times. The key stages in the formation of the profession are examined, including the early practices of nursing, the organization of nursing in medieval monasteries, and the significance of Florence Nightingale in the development of modern standards of nursing care. The results of statistical studies highlighting the relationship between the quality of nursing care and clinical outcomes, in particular, a decrease in mortality with an increase in the number of nurses per 10 patients, are also analyzed. In conclusion, current trends and prospects for the development of nursing are discussed, including the introduction of telemedicine and advanced training programs, which emphasizes the importance of this profession in the health care system.